2008
DOI: 10.1007/s10750-008-9286-3
|View full text |Cite
|
Sign up to set email alerts
|

Life history changes in Atlantic salmon from the River Dee, Wales

Abstract: The change in life history of Atlantic salmon (Salmo salar L.) on the River Dee over the last 60 years is described. Over the last 60 years, salmon have shown a change in run timing, the majority currently entering the river between August and October compared with prior to June. This has coincided with a change in the sea age composition, which was dominated by multi-sea winter salmon prior to the 1980s after which the proportion of 1sea-winter fish increased until they now dominate the mature population. Gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 42 publications
1
15
0
Order By: Relevance
“…The observed delay in migration timing ( c . 5–10 days per decade) is also congruent with previous findings in Scotland (Youngson et al ., ; Todd et al ., ), England (Aprahamian et al ., ) or Spain (Valiente et al ., ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The observed delay in migration timing ( c . 5–10 days per decade) is also congruent with previous findings in Scotland (Youngson et al ., ; Todd et al ., ), England (Aprahamian et al ., ) or Spain (Valiente et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, a decline in the proportion of late maturing fish has been reported for many European and North American stocks (Baglinière et al ., ; Otero et al ., ; ICES, ; Jonsson et al ., ). Those changes have been accompanied by a decline in length and mass of fish and a variation in age at maturity (Aprahamian et al ., ; Bacon et al ., ; Jonsson et al ., ) together with a delay in adult migration timing (Valiente et al ., ; Todd et al ., ). For instance, higher proportions of 1 sea‐winter (1SW) fish in the late 20th century and more multi‐sea‐winter (MSW) fish in this century have been reported by Jonsson et al .…”
Section: Introductionmentioning
confidence: 98%
“…Narayanan et al 1995 ) and may comprise a fundamental population response to climate change. For example, over the past 60 years in the River Dee, Wales, Aprahamian et al (2008) showed that most adults now re -enter between August and October as opposed to prior to June. This coincided with a shift from MSW domination prior to the 1980s to the present prevalence of the 1SW maturity grouping.…”
Section: Ocean C Limate I Nfl Uences On R Un -T Iming and A Dult A Bumentioning
confidence: 99%
“…; Aprahamian et al. ) may also have contributed to later runs. Reduced condition was indirectly associated with warming temperatures that may have contributed to decreased prey availability (Beaugrand & Reid ) such that salmon in some European rivers may be remaining at sea longer as a result of lower swimming stamina (Valiente et al.…”
Section: Discussionmentioning
confidence: 97%